DAMPAK PERNIKAHAN USIA MUDA DI KECAMATAN BATANG ANAI KABUPATEN PADANG PARIAMAN - Sonia Selviani; Paus Iskarni (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to: 1) determine the impact of young marriage on fertility in Batang Anai sub-district, Padang Pariaman district 2) find out the impact of young marriage on job acquisition in Batang Anai sub-district, Padang Pariaman district, and 3) find out the impact of young marriage on household income in Batang Anai District, Padang Pariaman Regency. This study used the mixed method. The data was colected by conducting interviews, observations, and documentation. Sources of data from this study using primary data obtained and collected by researchers directly in the field and using secondary data obtained from journals and related agencies. This study found: 1) The impact of young marriage on fertility in Batang Anai sub-district, Padang Pariaman district explain that the younger the age of young married couples, the higher the birth rate. 2) The impact of young marriage on job acquisition in Batang Anai sub-district, district Padang Pariaman based on the results of research, most of the husbands work as farmers and casual daily laborers. 3) The impact of young marriage on household income in Batang Anai District, Padang Pariaman Regency, based on the results of research on household income, most of them earn 1.5 million per month, so it can’t fulfill the needs and welfare of the households. Keywords: Marriage, Fertility, Employment, Income